Rotary mechanism of V/A-ATPases—how is ATP hydrolysis converted into a mechanical step rotation in rotary ATPases? - Yokoyama, Ken (Frontiers in Molecular Biosciences, 2023)
V/A-ATPase is a rotary molecular motor protein that produces ATP through the rotation of its central rotor. The soluble part of this protein, the V1 domain, rotates upon ATP hydrolysis. However, the mechanism by which ATP hydrolysis in the V1 domain couples with the mechanical rotation of the rotor is still unclear. Cryo-EM snapshot analysis of V/A-ATPase indicated that three independent and simultaneous catalytic events occurred at the three catalytic dimers (ABopen, ABsemi, and ABclosed), leading to a 120° rotation of the central rotor. Besides the closing motion caused by ATP bound to ABopen, the hydrolysis of ATP bound to ABsemi drives the 120° step. Our recent time-resolved cryo-EM snapshot analysis provides further evidence for this model. This review aimed to provide a comprehensive overview of the structure and function of V/A-ATPase from a thermophilic bacterium, one of the most well-studied rotary ATPases to date.